An??lise tridimensional do movimento de membros superiores com uso de pulseira de peso em adultos jovens sadios e com paralisia cerebral do tipo discin??tico - Artilheiro, Mariana Cunha (2011)
This study aimed at verifying how weight bracelets affects the performance movement when taking a cylindrical glass with 50 % in filling of its total volume up to the mouth. This study involved 11 healthy young adults (20.36 ?? 27.82 years old) and 16 patients with dyskinetic cerebral palsy (who composed the GPCD) (25.21?? 34.05 years old). Nine infrared cameras Vicon?? MX 40 (Oxford Metrics Group, Oxford, UK) were used for the initial and final task without weight, including 10 %, 20 %, 30 % of maximum weight and measured by using a manual dynamometer adapted for such task. How the weight affects the performance movement was assessed by using the time, smoothness and speed parameters and three-dimensional kinematic angle of the shoulder and elbow joint. Performing the movement without weight showed that patients with dyskinetic cerebral palsy move more slowly and less smoothly. Movements were also performed with more adduction and internal shoulder rotation, more elbow flexion and more forearm pronation concerning the healthy volunteers. The application of the loads in the GPCD found that they were not able to modify significantly the linear and angular variables involved in the movement of patients. However, when the movement execution with application of load on the GPCD was compared with healthy young adults, the results showed influence in going phase, going/returning relationship, average Jerk and skeweness of the linear parameters and angular variables of shoulder movements.